Pauci-Immune Necrotizing and Crescentic Glomerulonephritis with Membranous Lupus Nephritis, Fifteen Years after Initial Diagnosis of Secondary Membranous Nephropathy. (8th October 2015) - Burkhart, Ryan; Shah, Nina; Abel, Michael; Oliver, James D.; Lewin, Matthew
Abstract : Renal involvement in systemic lupus erythematosus (SLE) is usually immune complex mediated and may have multiple different presentations. Pauci-immune necrotizing and crescentic glomerulonephritis (NCGN) refers to extensive glomerular inflammation with few or no immune deposits that may result in rapid decline in renal function. We report a case of a 79-year-old Hispanic male with a history of secondary membranous nephropathy (diagnosed by renal biopsy 15 years previously) who was admitted with acute kidney injury and active urinary sediment. P-ANCA titers and anti-myeloperoxidase antibodies were positive. The renal biopsy was diagnostic for NCGN superimposed on a secondary membranous nephropathy. A previous diagnosis of SLE based on American College of Rheumatology criteria was discovered via Veteran's Administration records review after the completion of treatment for pauci-immune NCGN. ANCAs are detected in 20–31% of patients with SLE. There may be an association between SLE and ANCA seropositivity. In patients with lupus nephritis and biopsy findings of necrotizing and crescentic glomerulonephritis, without significant immune complex deposition, ANCA testing should be performed. In patients with secondary membranous nephropathy SLE should be excluded.